Heat Treatment of Additive Manufactured Metals - Yılmaz, Mustafa Safa; Özer, Gökhan (Springer, 2023)
Additive manufacturing systems, which have strict control processes before and after manufacturing, are used in many industries. The quality of the machine’s equipment and raw materials used directly affect the production parts characteristics and quality. Additive manufacturing parts, which give properties close to traditional production methods, require secondary processing mostly. Due to the nature of the process, AM parts have weaknesses. Although postproduction processes help correct some of these defects, it should be remembered that irreversible damage will occur by malicious applications. The most widely used and most reliable process after the production is heat treatment. In this section, the most commonly used additive manufacturing processes and heat treatments (as a postprocess) for metals (titanium, aluminum, steel, etc.) and the effects (microstructure, mechanical properties, corrosive properties, thermal properties) of the heat treatment processes on the material will be discussed. The most used heat treatments in additive manufactured metal product, stress-relieving annealing, solution annealing, ageing, over-ageing, etc., processes are examined in detail. Different heat treatment applications (atmospheric control, impurity level, pressure, etc.) may be required depending on the type of material used, production conditions and place of use (there are many rules in aviation and medical services). In some cases, second/third heat treatment applications may be required.
Keywords: Heat Treatment; Powder Bed Fusion; Microstructure; Mechanical Properties; Corrosion; Wear